Impact of groundwater abstraction on a Banksia woodland, Swan Coastal Plain,Western Australia. - Groom, Philip; Froend, R.; Mattiske, E. (2000)
The Gnangara Groundwater Mound, centred 38 km north of Perth, Western Australia, is a large, shallow unconfined aquifer that is currently under abstraction as part of the public metropolitan water supply. To investigate the impact of lowering groundwater levels on a Banksia woodland on the Mound, vegetation monitoring near a groundwater abstraction bore (known as P50) began 1 year before becoming operational. In February 1991, 2 years after abstraction commenced, extensive death of the Banksia overstorey was observed within close proximity of the bore, following a short period of high summer temperatures. The site was subsequently revisited and the understorey floristic composition, abundance and vigour of overstorey species resurveyed, and compared with data collected from a site under longterm monitoring and not currently influenced by abstraction. A lowering of groundwater level by 2.2 m at P50 between the summers of 1990 and 1991, resulting from the cumulative effects of abstraction and below average annual rainfall (low groundwater recharge), coincided with a loss of between 20 and 80% of adults of overstorey species and up to 64% of adults of understorey species within 200 m of the bore. Over a similar time period no significant decreases in the abundance of overstorey or understorey species were recorded in the monitored site not influenced by groundwater abstraction. Of the overstorey species, Holly-leaf Banksia (Banksia ilicifolia) displayed the greatest susceptibility and lowest net recovery following the abstraction event at P50. The negative impact of groundwater drawdown on Hollyleaf Banksia populations makes this overstorey species an important indicator of decreasing groundwater levels on the Gnangara Groundwater Mound. Water stress may have been the primary cause of vegetation death in close proximity to the P50 bore, although this would have been exacerbated by extreme summer temperatures (> 45°C) recorded during February 1991. The P50 scenario represents a localized response to an acute drawdown event, in association with other environmental factors, and provides invaluable information on the assessment of groundwater abstraction and poor groundwater recharge events on a Banksia woodland community. However, there are limitations in using the community response at P50 to manage the impact of drawdown events on other plant communities occurring on sandy, shallow aquifers.